Perubahan Komoditi dari Bertani Nilam ke Bertani Pisang Pada Masyarakat di Desa Aere Kecamatan Aere Kabupaten Kolaka Timur - Hadrianti, Rezky; koodoh, Erens E. (JURNAL KABANTI: Kerabat Antropologi, 2024)
This research aims to find out and describe the reasons for the transition from patchouli farming to banana farming in the community in Aere Village, Aere District, East Kolaka Regency and to describe the implications for the community of this change. Data collection was carried out using participant observation techniques and in-depth interviews. The data obtained was analyzed using adaptation theory according to John William Bennett. Data analysis is intended to simplify the data obtained so that it is easier to read and understand. The research results show that people who have switched from farming patchouli to bananas in 2021, have experienced economic sufficiency with an increase in their income. The transition that occurred in the Aere Village community was influenced by several things, namely; the production results of patchouli farmers are less than optimal, the land is no longer suitable for patchouli plants, the price of patchouli tends to fall, farming bananas is easier than patchouli, the types of bananas harvest bananas faster, and the price of bananas is relatively stable and market demand is high which makes people choose to switch commodities from patchouli farming to banana farming and have an impact on the economy which results in the movement or change in the position of a person or group at different times. And the social impact that occurs on the community, whether because an incident affects the community or other things within the community in Aere Village.